Evaluasi Kinerja dan Kepuasan Pengguna Sistem Informasi Akademik (SIAK) dengan Metode PIECES dan EUCS - Aditya Waras Utama (JURNAL CITRA WIDYA EDUKASI, 2018)
Academic Information System at the Politeknik Kelapa Sawit Citra Widya Edukasi still uses desktop systems. By applying that system, all college students get all administrative services easily and it doesn’t take long time. That is not the only problem solving of student administration, because students expect not only the speed but also the satisfaction in their use. In the globalization era, we hope that schools, universities, and polythenics use On-Line administration to meet the students demand. It is not enough if we only fulfill the users demand, that’s why writer tries to do research on application performance both in terms of hardware and software using PIECES method, while for satisfaction writer tries to use EUCS method. It was done at the Politeknik Kelapa Sawit Citra Widya Edukasi with respondents consist of all students, lecturers and staffs. From the result of the satisfaction of the respondents , we hope that we can improve and develope the software, and it will become more user friendly (easy to use).